Competences in the digital sphere of mechanical engineering specialists - Yevtushenko, N. S.; Vorobyov, M. M. (Державний біотехнологічний університет, 2024)
The digital transformation currently taking place inevitably affects the entire national economy, among which mechanical engineering occupies a special place. This level of development of mechanical engineering ultimately determines the industrial potential of the state. In no other industry does the introduction of advanced technologies and new equipment produce such rapid and significant results as in mechanical engineering. The introduction of digital technologies in mechanical engineering places new demands on workers. New digital competencies are needed by all employees: from workers to specialists. The use of digital technologies has long been the norm for engineering and technical workers in mechanical engineering. Automated design and development of design and technological documentation at most enterprises is carried out using application programs (application software packages). Text and spreadsheet editors (processors), automated calculation tools, etc. are actively used. Digital technologies have not yet received are widespread, but they also face problems with working with technical documentation in electronic form, using computer measuring systems, etc.
Keywords: digital competence; mechanical engineering; professional activity; professional standard